2011
DOI: 10.1029/2011gl048586
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of magnetic reconnection in a magnetosheath current sheet due to compression against the magnetopause

Abstract: We report in‐situ measurements by three THEMIS spacecraft showing the evolution of reconnection in a solar wind current sheet as the current sheet transited from the solar wind across the bow shock and close to the magnetopause on July 11, 2008. The observations suggest that the solar wind reconnection exhaust within the current sheet was disrupted by its interaction with the bow shock, while the subsequent compression of the current sheet against the magnetopause significantly reduced both the current sheet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…It is also consistent with a reported magnetosheath event with the guide field roughly equal to the reconnecting field, which showed only parallel heating but no perpendicular heating [Phan et al, 2011].…”
Section: Summary and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is also consistent with a reported magnetosheath event with the guide field roughly equal to the reconnecting field, which showed only parallel heating but no perpendicular heating [Phan et al, 2011].…”
Section: Summary and Discussionsupporting
confidence: 80%
“…Heating observed in near-Earth magnetotail exhausts tends to be roughly isotropic [e.g., Chen et al, 2008], while a magnetosheath exhaust reported by Phan et al [2011] showed only parallel heating. These striking differences in the electron heating properties in different regions in space suggest that the degree and anisotropy of electron heating depend strongly on plasma parameter regimes and/or boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Symmetric reconnection with a variety of guide fields often occurs in solar wind current sheets [e.g., Gosling et al ., ; Gosling and Szabo , ; Phan et al ., ; Gosling and Phan , ], but the observations are usually far downstream of the X line. In recent years, symmetric reconnection has also been reported in current sheets in the magnetosheath [e.g., Retino et al ., ; Phan et al ., , , ], but some of these thin current sheets were not resolved by past plasma measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[30] It is also likely that the current sheet is compressed more strongly at its part closer to, rather than farther from, the magnetopause [Phan et al, 2011]: the reconnection rate may well be higher at an X-line nearer to the magnetopause. Such location-dependent reconnection may have pushed the resulting flux rope sunward and have enhanced the sunward flow in the magnetosheath HFA.…”
Section: Discussionmentioning
confidence: 99%